Deformation in volcanic areas: a numerical approach for their prediction in Teide volcano (Tenerife, Canary Islands) - Charco, María; Galán del Sastre, Pedro (Física de la Tierra, 2012)
Active volcanic areas study comprises both, observation of physical changes in the natural media and the interpretation of such changes. Nowadays, the application of spatial geodetic techniques, such as GPS (Global Positioning System) or InSAR (Interferometry with Synthetic Aperture Radar), for deformation understanding in volcanic areas, revolutionizes our view of this geodetic signals. Deformation of the Earth’s surface reflects tectonic, magmatic and hydrothermal processes at depth. In this way, the prediction of volcanic deformation through physical modelling provides a link between the observation and depth interior processes that could be crucial for volcanic hazards assessment. In this work, we develop a numerical model for elastic deformation study. The Finite Element Method (FEM) is used for the implementation of the numerical model. FEM allows to take into account different morphology, structural characteristics and the mechanical heterogeneities of the medium. Numerical simulations of deformation in Tenerife (Canary Islands) taking into account different medium hypothesis allow us to conclude that the accuracy of the predictions depends on how well the natural system is described.